THERAPEUTIC USES OF NASYA KARMA: CONCEPTUAL CRITICAL REVIEW (International Journal of Ayurveda and Pharma Research, 2020)
Nasa (Nose) is an Indriya, which works not only to perceive the smell but also to provide the main breathing pathway, along with this, Nasa is one of the drug administration pathways. Acharyas have been placed Nasya as one of the Panchkarma procedures, which signify the importance of Nasya as Shodhana Karma (Purification procedure) especially for Urddhva-jatrugata Vikara (disease which affect the body above clavicle). Nasya Karma is a therapeutic measure in which the drug (Medicated Oil/Ghee/ Decoction/ Powder/Smoke etc.) is administered by Nasa (Nose) essentially to remove the vitiated Dosha found in Shira and its constituent parts. Indirectly, by enhancing the functions of the endocrine glands and nervous system, Nasya can operate on the entire body. In classics Nasya is mentioned in different type of supra-clavicular as well as in systemic diseases. So present review article focused on the therapeutic uses of Nasya Karma in different diseased condition which are proven by clinical researches.